2015
DOI: 10.2355/isijinternational.55.1135
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Carbon Content on Toughening in Ultrafine Elongated Grain Structure Steels

Abstract: (0.2-0.6)%C-2%Si-1%Cr-1%Mo steels were quenched and tempered at 773 K and deformed by multipass caliber rolling (i.e. warm tempforming) with a rolling reduction of 78%, in order to obtain ultrafine elongated grain (UFEG) structures. The tensile and Charpy impact properties of the warm tempformed (TF) steels were investigated to determine the influence of the carbon content on toughening in the UFEG structures. The TF samples consisted of UFEG structures with strong <110>//rolling direction (RD) fiber textures.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(55 citation statements)
references
References 19 publications
(43 reference statements)
1
53
1
Order By: Relevance
“…This is commonly observed in the WTF steels. [7][8][9][10][11] In astempered state, the AF sample has higher σ y and σ B than the non-AF sample. For the AF sample, the WTF with a rolling reduction of 46% causes an increase in the σ y but not in the σ B .…”
Section: Tensile Propertiesmentioning
confidence: 99%
See 4 more Smart Citations
“…This is commonly observed in the WTF steels. [7][8][9][10][11] In astempered state, the AF sample has higher σ y and σ B than the non-AF sample. For the AF sample, the WTF with a rolling reduction of 46% causes an increase in the σ y but not in the σ B .…”
Section: Tensile Propertiesmentioning
confidence: 99%
“…4(g)-4(i)) reveals that the non-AF and AF samples have an almost similar distribution of spheroidized carbide particles after the WTF with rolling reductions ranging 46% to 74%. It has been commonly observed that carbide particles grew slightly, becoming more spherical during the WTF at 773 K. [8][9][10][11] Furthermore, strong < 110 > //RD fiber textures are developed through the WTF (Figs. 4(j)-4(l)).…”
Section: Microstructural Characterization and Mechanicalmentioning
confidence: 99%
See 3 more Smart Citations